The Healthy Eating Indices of Puerto Rican Families, 1961 to 1966: A Retrospective Study, Calculated using Data from Previous Nutritional Surveys - Preston, Alan M. (Puerto Rico Health Sciences Journal, 2025)
The 1960’s were a transitional period in Puerto Rico. Advances in the betterment of the human condition was measurable, especially in highly populated areas but less so in isolated communities. To obtain a more exact picture of conditions in these communities, a committee was established to conduct surveys that would give information on the standard of living with special emphasis on nutrition. Families from barrios in 8 isolated municipalities were selected by random sampling and questioned about their economic situation, home conditions, general health and food consumption. Next, an island-wide survey asked the same questions, but sampling was conducted using a stratified Master Sample so that findings would apply to the population as a whole. This article incorporates combined results from these nine surveys. The Healthy Eating Indices (HEIs) for the isolated municipalities and for the Master Sample averaged 58 and 66, respectively. Both are classified as “Needs Attention” however, caloric intake in the isolated areas was only about three fourths that of the Master Sample and more than one third of these calories came from lard and sugar. Overall, of the 13 components of the HEI, 4 obtained “satisfactory” scores while 4 were scored as “deficient.” These scores, although still needing improvement, show a greater compliance with recommendations of the HEI than those found in the 2015 US population where overall score was 57 with only 2 components having a “satisfactory” score while 4 components were also being classified as “deficient.”